Gut microbiome-mediated health effects of fiber and polyphenol-rich dietary interventions - Meiners, Franziska; Ortega-Matienzo, Asiri; Fuellen, Georg; Barrantes, Israel (Frontiers in Nutrition, 2025)
Dietary components substantially influence aging-related health outcomes through the interaction with the gut microbiome. In this narrative review, we compiled human dietary intervention trials with varying complexities: from simple modifications like the addition of herbs and spices, nuts and beans, to whole-diet patterns such as the calorie-restricted high-polyphenol Green-Mediterranean diet. We show that the addition of fiber- and polyphenol-rich foods consistently enrich short-chain fatty acid (SCFA) producing bacteria such as Faecalibacterium, Eubacterium, Roseburia, and Blautia, and modulate various plasma and fecal metabolites, including increased levels of propionic acid when combining nuts with caloric restriction, increased visceral fat loss mediated by urolithins, and enhanced anti-inflammatory effects, potentially due to synergistic action between SCFAs and polyphenol metabolites. Furthermore, we highlight that relatively simple dietary modifications can produce meaningful microbiome and metabolite shifts, particularly in elderly and metabolically compromised populations, where the microbiome may be more responsive to intervention, and intervention effects are more pronounced. When added to strategies like caloric restriction, these foods can help preserve microbial diversity, maintain beneficial taxa, and enhance anti-inflammatory effects. These insights can inform the development of microbiome-targeted dietary strategies for improving health in high-risk populations.